Optimization studied for the sugar production from rice husk by using enzymatic hydrolysis - Nur Faizah Abdul Majid (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
The optimization of glucose content in rice husk using enzymatic hydrolysis was investigated in the study. Single factorial design and Central Composite Design (CCD) were used as a statistical tool to screen the range of the selected parameters and to optimize the process respectively. Three parameters which are particle size, dosage of enzyme and times were optimizing. Rice husk was treated with physical treatment method using a grinder before sifted to obtain different particle size. Enzymatic hydrolysis was conducted in the orbital shaker with 150 rpm using celluclast enzyme 1.5 L. In order to determine the glucose concentration, DNS (3, 5-dinitrosalicylic) analysis method was conducted. The absorbance value of the analysis sample was determined using spectrophotometer at wavelength 545 nm. By using CCD, the optimum values were obtained at 0.29 mm, 566.25 L and 14.25 hours for particle size, dosage of enzyme and times, respectively, to give an optimum glucose content of 5.443 g/L.